The mTORC1 Signaling Support Cellular Metabolism to Dictate Decidual NK Cells Function in Early Pregnancy - Yan, Song; Dong, Jie; Qian, Chenxi; Chen, Shuqiang; Xu, Qian; Lei, Hui; Wang, Xiaohong (Frontiers in Immunology, 2022)
Cellular metabolism plays an important role in regulating both human and murine NK cell functions. However, it remains unclear whether cellular metabolic process impacts on the function of decidual NK cells (dNK), essential tissue-resident immune cells maintaining the homeostasis of maternal-fetal interface. Remarkably, we found that glycolysis blockage enhances dNK VEGF-A production but restrains its proliferation. Furthermore, levels of IFN-γ and TNF-α secreted by dNK get decreased when glycolysis or oxidative phosphorylation (OXPHOS) is inhibited. Additionally, glycolysis, OXPHOS, and fatty acid oxidation disruption has little effects on the secretion and the CD107a-dependent degranulation of dNK. Mechanistically, we discovered that the mammalian target of rapamycin complex 1 (mTORC1) signaling inhibition leads to decreased glycolysis and OXPHOS in dNK. These limited metabolic processes are associated with attenuated dNK functions, which include restricted production of cytokines including IFN-γ and TNF-α, diminished CD107a-dependent degranulation, and restrained dNK proliferation. Finally, we reported that the protein levels of several glycolysis-associated enzymes are altered and the mTORC1 activity is significantly lower in the decidua of women with recurrent pregnancy loss (RPL) compared with normal pregnancy, which might give new insights about the pathogenesis of RPL. Collectively, our data demonstrate that glucose metabolism and mTORC1 signaling support dNK functions in early pregnancy.